2021
DOI: 10.2298/jmmb200622010w
|View full text |Cite
|
Sign up to set email alerts
|

A new method for determination of the theoretical reduction amount for wide-thick slab during the mechanical reduction process

Abstract: Mechanical soft reduction (MSR) is an effective method to eliminate the centerline segregation and porosity of the continuous casting steel slab, and the reduction amount is a key parameter that determines whether the MSR could be applied successfully. In the present work, a 2D heat transfer model was developed for predicting the non-uniform solidification of the wide-thick slab. The measured shell thickness by nail shooting experiment and the measured slab surface temperature by infrared cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Further studies indicated that the chalcopyrite leaching was very dependent on the hydrogen peroxide concentration. 106 The reaction mechanism is diffusion controlled through a protective sulfur layer at lower temperatures, and controlled by the surface chemical reaction at temperatures in excess of 55 °C. Other oxidizing agents have been added to MSA to enhance the leaching kinetics of chalcopyrite in MSA.…”
Section: Copper Hydrometallurgymentioning
confidence: 99%
“…Further studies indicated that the chalcopyrite leaching was very dependent on the hydrogen peroxide concentration. 106 The reaction mechanism is diffusion controlled through a protective sulfur layer at lower temperatures, and controlled by the surface chemical reaction at temperatures in excess of 55 °C. Other oxidizing agents have been added to MSA to enhance the leaching kinetics of chalcopyrite in MSA.…”
Section: Copper Hydrometallurgymentioning
confidence: 99%
“…The presence of fluoride ions increases oxide solubility. Solubility of REM oxides in molten salts was mostly studied with the aim of selecting a suitable oxide-fluoride electrolyte for electrowinning rare earth metals (2)(3)(4)(5)(6)(7)(8)(9). Such electrolytes always contained fluoride of the corresponding REM as one of the components.…”
Section: Introductionmentioning
confidence: 99%